Comparison of Time to Remission in Treatment Regimen at Remission between Late Onset Rheumatoid Arthritis (LORA) and Early Onset Rheumatoid Arthritis (EORA) Patient - Akram, Ishwah; Zubair, Muhammad; Bukhari, Syeda Kinza; Khan, Fahad Ahmad; Maheen, Aima; Ijaz, Hasaan (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the time to remission and treatment regimen at remission between late onset rheumatoid arthritis (LORA) and early onset rheumatoid arthritis (EORA) patients. Study design: Prospective cohort study. Place of duration of study: Department of Medicine, CMH, Multan from July 2023 to December 2024. Methods: A total of 670 patients with an age of onset of active RA ≥ 60 years, diagnosed within 1 year, were included in the LORA group. Other 670 patients with age of onset of active RA between 18-59 years with similar diagnostic details were included in the EORA group. Disease activity was evaluated using the DAS -ESR 28 score. Patients initiated methotrexate (5-15mg/week, maximum 25mg/week). Upon inadequate response to optimal therapy, (DAS28-ESR ≥ 2.6 after 3-6 months), tofacitinib (5mg twice daily) was added to methotrexate or used as monotherapy in intolerant cases, following treat-to-target strategy. The primary outcomes were set as DAS28-ESR scores, proportion of patients achieving remission (DAS28-ESR < 2.6) at 12 months, time to first remission, and treatment regimens at remission. Results: The mean age of patients was 68.35±5.99 and 49±5.89 years in group LORA and group EORA respectively. LORA patients were more frequently on methotrexate monotherapy (p=0.04) or methotrexate + tofacitinib combination (0.004) than EORA patients. There was no statistically significant difference in the two groups in DAS28-ESR score achieved and the number of patients achieving DAS28-ESR ˂2.6 at the completion of study. Comparison of time to remission in patients achieving remission also showed no statistically significant difference among the two groups (p=0.5). Conclusion: The remission rate and time to remission remains similar in LORA and EORA patients despite the differences in medication regimens to achieve remission.